PENGGUNAAN VIDEO TERHADAP PENINGKATAN TES HASIL BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI KELAS XI IPS SMAN 1 PASAMAN BARAT - Hermita, Lisa - (Pendidikan Sosiologi, 2014)
This research is motivated by studentsâ learning result in subject low sociology at eleventh grade of Social science Senior High School West Pasaman. The purpose of this research to know by using video to increase the studentsâ result in eleventh grade social science Senior High School West Pasaman. The type of this research is experimental research, while in learning process of this research should be done on two class that are experimental class and control class. The selection of sample in this research was take based on the random, so that class experimental obtained by eleventh grade social science four and control class is eleventh grade social science two. After the study can be found that the use of video in learning have a significant effect on studentsâ result in sociology subject, itâs seen from the average results of studying experimental class was 79, 97 with a standard deviation of 8,46 of a control class average was 67, 81 with a standard deviation of 10,89 test result t count results are 3,32test results to 0,05 significance level obtained t table 1.67 then t t count more greater than t count which means that the hypothesis is accepted. From the analysis of the research and discussion is concluded that the use of video in learning have a significant effect on studentâs learning result in subjects of sociology at Senior High School Pasaman. Therefore it was concluded that the teachers can use video in learning process.